Pentingnya Manajemen SDM dalam Menciptakan Lingkungan Kerja yang Produktif - Setyo Budi Pulungan (PT. Hasba Edukasi Mandiri, 2025)
Human Resource Management (HRM) plays a crucial role in creating a productive work environment. Effective HRM involves various aspects, such as proper recruitment, employee training and development, fair reward systems, and effective leadership. However, many companies face challenges in managing human resources, including high turnover rates, low work motivation, and adapting to technological changes. Using a qualitative approach with a case study method, this research analyzes how effective HRM can enhance work productivity and employee well-being. The findings indicate that companies implementing data-driven HR strategies, inclusive leadership, and flexible employee welfare programs achieve higher productivity levels. By optimizing HR management, organizations can create a more innovative, sustainable, and competitive work environment.